PERAN KETERBUKAAN DIRI DALAM MEMEDIASI PENGARUH INTENSITAS KOMUNIKASI INTERPERSONAL TERHADAP SUBJECTIVE WELL-BEING PASANGAN YANG MENJALANI HUBUNGAN KENCAN BERBASIS ONLINE - Mimi Sakinah Hilma; Yanuar Luqman; Triyono Lukmantoro (Interaksi Online, 2023)
Advances in communication technology in the current era create a new trend, namely online-baseddating. This trend provides an opportunity for someone to build relationships, share affection and establish intimate relationships on an online basis. But in reality, not everything that happens on conventional dating can also be done online. This is what then can affect the subjective well-being of couples who undergo online-based dating relationships. Communication that connects partners can create comfort if it goes well and conversely communication can be a source of vulnerability in online-based dating if it doesn't go well. In the process, self-disclosure is believed to be a factor that influences the communication process between the couple. This study uses social penetration theory to explain each variable. The sampling technique was purposive sampling, totaling 250 people aged 18-29 years and had experienced online-based dating relationships. Tests in this study using linear regression. The results showed that the effect of the intensity of interpersonal communication on self-disclosure was 37.7%. Then the effect of self-disclosure on subjective well-being is 56.7%. Not only that, the results of the study also show that self-disclosure has a mediating effect on the effect of the intensity of interpersonal communication on subjective well-being directly.